Citrullinemia and Hyperglycinemia Presenting with Seizures - Case Report of a 4 Day Old Baby - Lodh, Moushumi; Kerketta, Joshi Anand (Asian Journal of Medical Sciences, 2013)
Inborn errors of amino acid metabolism (IEM) are of concern in India, the spectrum being wide, varied and poorly diagnosed. Since aggregate incidence of inborn errors of metabolism is relatively high, in countries such as India, a high degree of suspicion is essential to correctly diagnose an inborn error of amino acid metabolism. We report a case of citrullinemia, glycinemia with hyperammonaemia and seizures in a 4-dayold previously asymptomatic baby, with a brief review of the literature. DOI: http://dx.doi.org/10.3126/ajms.v3i1.4801 Asian Journal of Medical Sciences 3(2012) 17-20